2014
DOI: 10.1155/2014/492138
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant Antifungal Activity ofCorymbia citriodoraandCymbopogon nardusEssential Oils and Citronellal against Three Fungal Species

Abstract: Corymbia citriodora and Cymbopogon nardus essential oils samples were analyzed by GC and GC-MS and their qualitative and quantitative compositions established. The main component of essential oils of C. citriodora and C. nardus was citronellal, at 61.78% and 36.6%, respectively. The essential oils and citronellal were tested for their fumigant antifungal activity against Pyricularia (Magnaporthe) grisea, Aspergillus spp., and Colletotrichum musae. The minimum inhibitory concentration (MIC) ranged from 100 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 30 publications
4
28
0
6
Order By: Relevance
“…The germination of P. digitatum spores was also visibly inhibited by citronellal at concentrations higher than 0.20 lL/mL. This result was in agreement with previous reports describing the antifungal activity of citronellal (Nakahara et al 2013;Aguiar et al 2014). Interestingly, citronellal at a concentration of 0.050 lL/mL could stimulate the germination of P. digitatum spores.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The germination of P. digitatum spores was also visibly inhibited by citronellal at concentrations higher than 0.20 lL/mL. This result was in agreement with previous reports describing the antifungal activity of citronellal (Nakahara et al 2013;Aguiar et al 2014). Interestingly, citronellal at a concentration of 0.050 lL/mL could stimulate the germination of P. digitatum spores.…”
Section: Discussionsupporting
confidence: 92%
“…In recent studies, citronellal has been observed to be one of the principal components in some plant essential oils and showed good antifungal activity against the pathogen that cause severe destruction in apple, tomato and banana (Aguiar et al 2014;Arancibia et al 2014). Thus, citronellal might be a potential antifungal substance in controlling postharvest disease of citrus fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Both the poisoned food and disc diffusion bioassays revealed that the EO of E. camaldulensis inhibited the growth of the test fungi in a dose-dependent manner. There are many reports in literature of concentration-dependent antifungal activity of essential oil whereby the colony diameters increase with decrease in the concentration of EO (poisoned food bioassay) or the diameters of the inhibition zone increase with increase in the concentration of the essential oil (disk diffusion assay) [35, 36]. Some exceptional instances were however observed in the current study such as in the case of F. solani and F. proliferatum where undiluted EO produced smaller inhibition zones in comparison to diluted essential oil.…”
Section: Discussionmentioning
confidence: 99%